STRATEGI KOMUNIKASI PENYULUH AGAMA ISLAM DALAM PENGUATAN KEIMANAN MUALLAF KALORAN, TEMANGGUNG, JAWA TENGAH - Mukti Ali; Susi Ratna Sari; Reza Ahmadiansah; Win Listyaningrum Arifin (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
This study aims to determine the strategy of preaching Islamic religious instructors in an effort to maintain the values ​​of the faith of converts to Islam in Getas Village, Kaloran District, Temanggung Regency. By using a qualitative research approach. The results of this study show that 1) the number of converts to Islam in 2019 reached 37 people. Meanwhile, in 2020 the number of converts to Islam in Kaloran District has increased, namely as many as 43 converts who have faith in the KUA of Kaloran District. As for the number of converts in Getas Village itself, there are 10 converts based on the Islamic charter he obtained. Seeing the condition of converts who are classified as still unstable in their level of faith, a special strategy is needed to provide assistance to converts. 2) The da'wah strategy used by the Islamic religious instructor in Getas Village is to establish a special taklim assembly for the guidance of converts. 3) Establishing a Children's Learning House (RBA). 4) Provide motivation to converts by using the da'wah method bil-lisan and bil-hal. 5) Strengthening the economy of independent converts through the program (M.Tri).